STRATEGI ADAPTASI PEKERJA TOKUTEI GINOU INDONESIA: STUDI KASUS INDUSTRI PERHOTELAN HOKKAIDO - Rizkiawan Pratama, Tubagus; Srimulyani, Nunuk Endah (Universitas Airlangga, 2024)
Indonesian Migrant Workers with tokutei ginou (specified skilled worker) visas in Japan experience problems and obstacles while working in Japan. To overcome these problems, they carry out adaptation strategies for each problem. This study aims to find out the problems of Indonesian migrant workers in Japan and how to adapt to these problems. This research is descriptive qualitative research and uses a case study approach. The objects in this research are three Indonesian Migrant Workers with tokutei ginou visas who work in the hospitality industry in Hokkaido, Japan. In collecting data, in-depth interviews were conducted. The results of this research reveal that Indonesian migrant workers experience several problems while working in Japan, such as differences in habits, work culture, language barriers, environmental conditions, absence of places of worship, and incompatibility of work contracts. From these problems, the migrant workers have ways to deal with these problems in order to adapt in Japan. Such as adjusting to the habits of Japanese society, relearning the Japanese language, familiarizing themselves with the weather conditions in Japan, and worshiping in their respective residences. It can be concluded that the adaptation strategies carried out by Indonesian migrant workers based on John William Bennett's theory are 1) adaptive behavior to adjust differences in habits; 2) adaptive strategy to deal with problems of work culture, language, environment, and religion; and 3) adaptive process to deal with work culture problems.